STUDI KOMPARASI SOAL BERBASIS KEMAMPUAN KONEKSI MATEMATIKA PADA BUKU TEKS SMA KELAS X KURIKULUM 2013 DAN KURIKULUM MERDEKA - Fitra Dewi Istiqomah; Dyana Wijayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematical connection skills are essential competencies that enable students to integrate various mathematical ideas, both internally and in external applications. This study aims to conduct a comparative study of the content of questions based on mathematical connection skills in the 2013 Curriculum (2017 Revised Edition) and the Independent Curriculum (2023 Revised Edition) for Grade X High School Textbooks. The research method used is descriptive quantitative with a content analysis approach to 350 questions. The analysis instrument refers to the NCTM (2000) standard, which has been used in Arina Susanty's 2018 research which includes: (1) connections between topics in mathematics, (2) connections between mathematics and other fields of science, and (3) connections between mathematics and everyday life, with an in-depth analysis of internal connection sub-indicators using the Hatisaru (2023) taxonomy. The analysis results show that there is a very significant difference in proportion between the two curricula, as strengthened by the Chi-Square test with a value of (2) = 26.554 and a significance value of p = <0,001 (p < 0.05). The 2013 Curriculum Textbook is dominated by connections between topics in mathematics by 77.5%, but has limitations in connections between mathematics and other fields of science and everyday life. In contrast, the Merdeka Curriculum Textbook shows a strengthening of connections between mathematics and everyday life by 26.7%. This indicates that the curriculum transition has brought about a change in the orientation of questions to be more applicable.